(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The use of natural polymers in the design of drug delivery formulation has received much attention due to their excellent biocompatibility and biodegradability. Among them, chitosan and gellan are very promising and have been widely exploited in pharmaceutical industry for controlled drug release. In the present study, an attempt has been made to formulate chitosan-gellan beads of Diltiazem hydrochloride using chitosan and gellan as ionic polysaccharide, and calcium chloride as cross-linking agent. The formulations were prepared by varying the concentration of gellan gum and chitosan. The prepared beads were evaluated for drug polymer interaction by FT-IR, DSC andsurface morphology by SEM. Drug content, swelling studies and in vitro drug release were carried out on prepared beads. FT-IR and DSC studies showed no interaction between drug and polymers. SEM showed spherical nature of beads with inward dents. Swelling of beads depends upon pH, concentration of polymers and crosslinking agent. The in vitro release of drug from beads was controlled for 12 h. Chitosan-gellan beads as controlled drug delivery were prepared by changing the polymer concentration. Swelling studies showed that with an increase in pH from acidic to basic, a considerable increase in swelling in all the formulations was observed.